PW 1782 An environmental scan of road safety policies in toronto, canada. (November 2018) - Fridman, Liraz; Rothman, Linda; Hagel, Brent; Howard, Andrew; Macpherson, Alison
Abstract : Background: Toronto introduced a Vision Zero Road Safety Plan (RSP) in 2017 with a goal of eliminating road traffic fatalities and serious injuries by 2021. A series of policies were published alongside the RSP with a focus on pedestrians, school children, and cyclists. While these documents provide insight into plans for future interventions targeted at vulnerable road users, little is known about the types of interventions that are most frequently recommended by policymakers and whether they are effective at reducing injuries. Objective: The purpose of this study was to identify and categorize the types of interventions outlined in city plans and/or policies directly related to traffic safety in Toronto, Canada. Methods: We performed an environmental scan of policies/plans that outline interventions such as regulatory changes and awareness campaigns with a focus on road traffic safety. Results: Our search yielded 26 policies with a purpose/objective statement on topics including the built environment, urban design, and active school transportation. Almost half (46%) were identified as being directly related to road traffic safety and were further summarized by intervention type, target population, cost, and whether the intervention was outlined in Toronto's Vision Zero RSP. A total of 107 interventions were identified in policy documents in Toronto. Forty three percent of interventions recommended modifications to the built environment (e.g. traffic calming measures). Interventions requiring a reduced speed limit from 50 km/h to 40 or 30 km/h were mentioned in 58% of policy documents in Toronto. Conclusions: Most interventions outlined in road safety policy documents in Toronto align with Vision Zero. Having identified the policies/plans that are recommended most often for implementation, these results will be used to prioritize naturalistic (quasi-experimental) research studies that demonstrate the effectiveness of specific interventions (e.g. speed limit reductions). Future studies will examine inter-municipal policy comparisons between Canadian provinces.